Antifibrotic action of pirfenidone and prednisolone: Different effects on pulmonary cytokines and growth factors in bleomycin-induced murine pulmonary fibrosis - Oku, Hisashi; Shimizu, Toshikatsu; Kawabata, Tomoji; Nagira, Morio; Hikita, Ichiro; Ueyama, Azumi; Matsushima, Shuuichi; Torii, Mikinori; Arimura, Akinori (European journal of pharmacology, 2008)
Pirfenidone, a broad-spectrum antifibrotic agent, is known to have efficacy in certain fibrotic disease models, and is under clinical trials in patients with idiopathic pulmonary fibrosis. We investigated the antifibrotic effect of pirfenidone, and its regulatory effect on various pulmonary cytokines, in bleomycin-induced lung fibrosis in mice at the protein level, using prednisolone as a reference agent. Pirfenidone attenuated the bleomycin-induced pulmonary fibrosis at a minimum effective dose of 30 mg/kg/day t.i.d. from the analysis of lung hydroxyproline content. Both pirfenidone (30, 100 mg/kg/day t.i.d) and prednisolone (3, 15 mg/kg/day q.d.) suppressed lung inflammatory edema; however, prednisolone failed to suppress pulmonary fibrosis, which was significantly suppressed only by pirfenidone. Both pirfenidone and prednisolone suppressed the increase in lung interleukin (IL)-1β, IL-6, IL-12p40 and monocyte chemoattractant protein (MCP)-1 levels induced by bleomycin. On the other hand, pirfenidone prevented the bleomycin-induced decrease in lung interferon (IFN)-γ levels, while prednisolone had no such effect. Furthermore, pirfenidone suppressed elevation of lung basic-fibroblast growth factor (bFGF) and transforming growth factor (TGF)-β1 levels, but prednisolone had no such effect. The increases in lung stroma cell derived factor (SDF)-1α and IL-18 were also suppressed. These findings suggest that pirfenidone exerts its antifibrotic effect through regulation of lung IFN-γ, bFGF and TGF-β1 levels during the development of bleomycin-induced pulmonary fibrosis in mice. The effect on SDF-1α and IL-18 levels may also be related to the antifibrotic effects of pirfenidone.